2014
DOI: 10.1371/journal.pone.0093368
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Microbial Contamination on Transvaginal Ultrasound Probes despite Low-Level Disinfection Procedure

Abstract: Aim of the StudyIn many countries, Low Level Disinfection (LLD) of covered transvaginal ultrasound probes is recommended between patients' examinations. The aim of this study was to evaluate the antimicrobial efficacy of LLD under routine conditions on a range of microorganisms.Materials and MethodsSamples were taken over a six month period in a private French Radiology Center. 300 specimens derived from endovaginal ultrasound probes were analyzed after disinfection of the probe with wipes impregnated with a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 25 publications
4
60
1
5
Order By: Relevance
“…Similarly, HPV was detected in six pre-examination samples. This study, as well as others, showed that a large amount of ultrasound probes were contaminated with high-risk HPV [57][58][59][60]. As discussed, most clinical disinfectants are inadequate to neutralize HPV.…”
Section: Potential Routes and Evidence Of Non-sexual Transmissionsupporting
confidence: 60%
See 1 more Smart Citation
“…Similarly, HPV was detected in six pre-examination samples. This study, as well as others, showed that a large amount of ultrasound probes were contaminated with high-risk HPV [57][58][59][60]. As discussed, most clinical disinfectants are inadequate to neutralize HPV.…”
Section: Potential Routes and Evidence Of Non-sexual Transmissionsupporting
confidence: 60%
“…As discussed, most clinical disinfectants are inadequate to neutralize HPV. Other studies looked at transvaginal ultrasound probes further and concluded that not only are they contaminated by HPV DNA, but also by free virions [59]. They determined this by treating swab samples with an exonuclease, which destroys all unprotected DNA.…”
Section: Potential Routes and Evidence Of Non-sexual Transmissionmentioning
confidence: 99%
“…Ethyl and propyl alcohol are effective decontaminants with success rates as high as 100 % [9] however, may damage the transducer, therefore Koibuchi et al [10] has suggested wiping the probes with a plain paper towel after every ultrasound examination, although to a degree that is not comparable with that obtained by using an alcohol-soaked paper towel. The other suggestion is wiping the probe with an alcoholsoaked paper towel before examination for patients with immunosuppression disease or after the examination of a patient with a skin infection, and at the end of each working day, additionally, the probe should be wiped with an alcohol-soaked paper towel [11].…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the risk of potential crosscontamination between the patients and the operator. 22,[26][27][28][29] Ensure that all cleaning agents used for the general environment have been approved by the equipment manufacturer.…”
Section: Equipment Cleaningmentioning
confidence: 99%
“…Several studies have examined the likelihood of transmission of this organism through transvaginal ultrasound using current infection control practices and found that transducer covers do not adequately prevent the contamination of transducers with HPVs 24 and that low-level disinfection may not remove HPV from ultrasound transducers. 22,24 Many other potentially infectious agents may be transmitted via improperly maintained, cleaned and disinfected ultrasound equipment, accessories and transducers, including protozoal pathogens such as Trichomonas vaginalis, intestinal parasites such as Entamoeba histolytica or fungal pathogens including dermatophytes and hyphomycetes.…”
mentioning
confidence: 99%